Kesadaran dan Persepsi Sertifikasi Halal pada UMKM Kuliner di Pasar Senggol Purwosari - Syafna Salsabila; M. Dayat; Ifdlolul Maghfur (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Halal awareness is a deep understanding possessed by Muslim consumers about halal products, in accordance with Islamic law and teachings. This understanding includes knowledge about the concept of halal, the halal production process, and how to ensure the halalness of products to be consumed. Muslim consumers tend to choose and consume halal products, considering that halal is not only about physical safety, but also the safety of belief. They prefer products that have been declared halal by an authorized institution (LPPOM MUI) because they feel safer and free from hazardous materials. Therefore, every Muslim is required to have halal awareness, because it reflects a deep understanding of the Islamic teachings that they believe in. Thus, halal awareness can be interpreted as a Muslim's understanding of the halal concept of a product in accordance with Islamic law. This study aims to examine the importance of halal awareness in improving the quality of culinary Micro, Small, and Medium Enterprises (MSMEs) services and the perception of halal certification, especially culinary MSMEs, in Pasar Senggol, Purwosari, Pasuruan Regency. The research method used is a qualitative case study with data collection techniques through surveys, interviews, and observations. The results of the study show that most culinary MSMEs understand the importance of halal certification and believe that it is a guarantee of quality and consumer trust. However, there are also some MSMEs that pay less attention to or even ignore halal certification. Culinary SMEs in Pasar Senggol Purwosari have the same thoughts about halal certification. They believe that obtaining a halal certificate is the personal responsibility of each business owner, not a shared responsibility. This means that they think that they themselves must decide whether they want to have a halal certificate or not, regardless of what other business owners do. This was revealed from interviews with several business owners.